Pengaruh Suhu Terhadap Kualitas Larva Dan Pertumbuhan Benih Gurami (Osphronemus gouramy) - Nurul Hidayah; Nunik Cokrowati; Alis Mukhlis (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Gouramy (Osphronemus gouramy) is a freshwater fishery commodity with a large enough demand and a fairly expensive price compared to other freshwater fish. The purpose of this study was to determine the effect of temperature on larval quality and growth of gouramy fry. The research method used is an experimental method using a Completely Randomized Design (CRD) consisting of two treatments of water media temperature, namely 1) Treatment A = The temperature of the media follows room temperature (control treatment), and 2) Treatment B = The temperature of the medium was set constant at a temperature of 30ᵒC. Each treatment was repeated six times to obtain 12 experimental units. Research parameter data were analyzed statistically using variance (ANOVA) at a 95% confidence level using the t-test. The results showed that the degree of hatching of gouramy eggs, larval size, absolute growth, relative growth, daily specific growth rate and survival rate of gouramy larvae at room temperature and 30°C were 90.38% and 98, respectively. 76%; 0.54 cm and 0.66 cm; 0.86 cm and 0.87 cm; 157.52% and 133.26%; 3.99% and 3.58%; and 74.78% and 91.22%. The study concluded that eggs incubated at room temperature (25-28°C) and 30°C gave significantly different effects on hatching rates and post-hatching larvae size. Larval rearing at room temperature and 30°C gave no significant effect on absolute growth but significantly different on relative growth, daily specific growth rate and survival rate